2012
DOI: 10.1103/physrevstab.15.010101
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent circuit for postcoupler stabilization in a drift tube linac

Abstract: Postcouplers (PCs) are devices used in order to reduce the effect of perturbations on the operating mode of a drift tube linac (DTL), using the resonant coupling stabilization method. In this article an equivalent circuit for a DTL equipped with PCs is presented, together with a 3D simulation analysis, which can explain the principle of postcoupler stabilization and define a new tuning strategy for DTL cavities. The PC tuning procedure based on the equivalent circuit and on frequency measurements has been test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…It is shown that zero admittance leads to a stabilized field distribution. The same stabilization point is found in [16] by a transport matrix notation. There the numerical model is fitted to modal measurements by adjusting the post-coupler parameters.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is shown that zero admittance leads to a stabilized field distribution. The same stabilization point is found in [16] by a transport matrix notation. There the numerical model is fitted to modal measurements by adjusting the post-coupler parameters.…”
Section: Introductionsupporting
confidence: 75%
“…In order to better understand the cavity behavior, equivalent-circuit models have been derived and its parameters extracted [5,[13][14][15][16]. Two resonance conditions are discussed in [5] with zero and infinite coupling admittance that will be rediscussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to perform the field tuning a relation needs to be made between the desired and measured fields of the cavity and the dimensions of the tuners. In general many tuner algorithms for accelerator cavities are based on equivalent circuit models [5][6][7]. This is also the case for RFQs, where the measurable field errors, usually obtained using the standard bead-pulling technique, are described as elements of the circuit [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…References [7][8][9] propose an equivalent circuit model for the DTL with the symmetrical PCs, further, this article improves the model so that field distribution and stabilization with asymmetrical PCs will be analyzed and the rate of the tilting field can be estimated. 2 The equivalent circuit for general periodic structure Figure 2, which is composed of equivalent parallel admittance Y n and series impedance Z n .…”
Section: Introductionmentioning
confidence: 99%